IDENTIFIKASI MISKONSEPSI SISWA DALAM MENYELESAIKAN SOAL TIMSS KONTEN ALJABAR DITINJAU DARI TINGKAT KECEMASAN MATEMATIKA - Isyam, Yufida Afkarina Nizar; Susanto, S; Oktavianingtyas, Ervin (Department of Mathematics Education , University of Jember, 2019)
This study aims to identify students’ misconception in terms of mathematics anxiety level. The type of this study was descriptive research with qualitative approach. The methods of data collection in this study used questionnaire, test, and interview. The subjects of this study were VIIIA grade students of Islamic Junior High School 2 Banyuwangi. Students’ test results are analyzed using four-tier diagnostic test to determine students understand the concept, do not understand the concept, and misconception. All students who have low mathematics anxiety level tend to understand the concept, students who have high mathematics anxiety level tend to do not understand the concept, while students who have middle mathematics anxiety level identified as misconception, but there were some who do not understand the concept and also understand the concept. Students’ tes results who identified as misconception were analyzed according to indicators of misconception. In this study the percentage of each form of students’ misconception to solve TIMSS problems with the total 31 students, 29% translation misconception or as many as 9 students, 16.1% of operation misconception or as many as 5 students, 29% of calculate misconception or as much 9 students, 16.1% systematic misconception or as many as 5 students, 12,9% concept misconception or as many as 4 students, and 22.6% of strategy misconception or as many as 7 students. Keywords: Algebra, Mathematics Anxiety Level, Misconception, TIMSS